The level of sex and fertility hormones in the serum of male patients recovered from COVID-19 - M. K. Albayaty; M. S. Ali; A. Y. AL-Tarboolee; R. H. Yousif (The Ukrainian Biochemical Journal)
The new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that generated the COVID-19 pandemic is a broad-spectrum infection that besides the respiratory tract, can attack multiple organs, including the digestive, circulatory, and urinary systems. However, the negative consequences of SARS-CoV-2 on the male reproductive system have been largely ignored. The aim of this research was to see how SARS-CoV-2 affects the production of hormones, which are the markers of male reproductive function and fertility. The 350 Iraqi male participants were classified into two groups consisting of 150 COVID-19 recovered patients with a mean age of (32 ± 7.9) years and COVID-19 diagnosis confirmed by RT-PCR, and 200 apparently healthy male volunteers of similar age. The patients’ group was further divided into three groups depending on the recovery period of 3, 5 and 7 months. Serum levels of testosterone, luteinizing hormone (LH), follicle stimulating hormone (FSH) and prolactin were measured using the Mindray CL-1000i automated chemiluminescence analyzer provided with matching kits. When comparing the indices of COVID-19 recovered participants to the control group, the results revealed a decrease in testosterone level that was positively associated with the recovery period and an increase in the LH, FSH and prolactin levels that were negatively associated with the recovery period. It is supposed that infection with SARS-CoV-2 may be followed by a temporary condition of testicular failure.